MECHANICAL DESIGN OF PRESSURE VESSEL BY USING PASSAT SOFTWARE COMPLEX - Федірко, П. П.; Девін, В. В.; Ткачук, В. С. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Pressure vessel is widely used in various industries. Reliability; safety of workers; productivity depend on its design. The peculiarity of the design of these devices is that their calculation is regulated by numerous regulations such as the state and industry standards; norms; and the like. The result of the present work is the conclusion that the software package "Passat" can be successfully applied to assess the strength of the high-pressure equipment. Using "Passat" for such calculations enables to fulfill all requirements of the applicable regulations. It will reduce metal equipment; increase operational reliability and reduce costs; and finally; it will improve the quality of the products. Application of the "Passat" program in the calculation of the design stage will allow the developer to find the optimal geometric shape and size of construction sites; based on the actual operating loads in the process of operation that is not always possible to fulfill using analytical dependences.